Level of green maize affecting methane production on roughage based diet - SINGH, G P; MOHINI, MADHU (The Indian Journal of Animal Sciences, 2012)
Effect of different levels of green maize fodder in wheat straw diet on IVDMD and methane production was studied. Rumen fistulated male crossbred animals (9) fed on green maize fodder and wheat straw (50:50) were used as donor animals. IVDMD, total gas and per cent methane in gas on 0, 5, 40, 60, 80 and 100% green maize fodder in substrate were estimated using rumen liquor of 4 donor animals. TVFA and individual fatty acids were also estimated. Methane production (litre/kg DDM) was calculated from the digestibility and methane production during fermentation. Methane production for growing, adult and lactating cattle were also calculated. Gas production increased from 95.8±3.16 to 123.9± 1.88 litre/kg. DDM because of increase of green maize fodder from 0 to 100% in substrate. Similarly the IVDMD increased from 42.8±0.53 on 0% maize fodder to 73.4±3.49% on 100% maize in diet. Both gas production and IVDMD increased linearly with the increase of fodder in wheat straw based substrate. However, while methane per cent in gas decreased from 43.1 to 26.3%, methane production (litre/per kg DDM) decreased from 43.1 to 32.6 litre due to supplementation of green maize fodder in diet. Methane production per kg milk production decreased with the increase of milk production level because of dilution of maintenance energy requirement.